Sertraline for the treatment of depression in Alzheimer’s disease: Week-24 outcomes - Weintraub, Daniel (2010)
BACKGROUND: Depression and antidepressant use are common in Alzheimer’s disease (AD), but the effect of antidepressant treatment for depression on longer-term outcomes is unknown. We report the week-24 outcomes of patients who participated in a 12-week efficacy study of sertraline for depression of AD. METHODS: 131 participants (sertraline=67, placebo=64) with mild-moderate AD and depression participated in the study. Patients who showed improvement on the modified Alzheimer’s Disease Cooperative Study Clinical Global Impression-Change (mADCS-CGIC) after 12 weeks of randomized treatment with sertraline or placebo continued double-blinded treatment for an additional 12 weeks. Depression response and remission at 24 weeks were based on mADCS-CGIC score and change in Cornell Scale for Depression in Dementia (CSDD) score. Secondary outcome measures included time to remission, non-mood neuropsychiatric symptoms, global cognition, function, and quality of life. RESULTS: 117 (89.3%) participants completed all study assessments and 74 (56.5%; sertraline=38, placebo=36) completed all 24 weeks on randomized treatment. By 24 weeks, there were no between-group differences in depression response (sertraline=44.8%, placebo=35.9%; odds ratio [95% CI]=1.23 [0.64, 2.35]), change in CSDD score (median difference=0.6 [95% CI −2.26, 3.46], χ(2) [df=2]=1.03), remission rates (sertraline=32.8%, placebo=21.8%; odds ratio [95% CI]=1.61 [0.70, 3.68]), or secondary outcomes. Common SSRI-associated adverse events, specifically diarrhea, dizziness, and dry mouth, and pulmonary serious adverse events (SAEs) were more frequent in sertraline-randomized patients than in placebo subjects. CONCLUSIONS: Sertraline treatment is not associated with delayed improvement between 12 and 24 weeks of treatment and may not be indicated for the treatment of depression of AD.